2022
DOI: 10.15252/embr.202154277
|View full text |Cite
|
Sign up to set email alerts
|

GSDMD drives canonical inflammasome‐induced neutrophil pyroptosis and is dispensable for NETosis

Abstract: Neutrophils are the most prevalent immune cells in circulation, but the repertoire of canonical inflammasomes in neutrophils and their respective involvement in neutrophil IL-1b secretion and neutrophil cell death remain unclear. Here, we show that neutrophiltargeted expression of the disease-associated gain-of-function Nlr-p3 A350V mutant suffices for systemic autoinflammatory disease and tissue pathology in vivo. We confirm the activity of the canonical NLRP3 and NLRC4 inflammasomes in neutrophils, and furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 61 publications
(153 reference statements)
4
44
0
Order By: Relevance
“…Nonetheless, our study did not exclude other mechanisms that might also be involved in the GSDMD-mediated lung injury upon LPS challenge. Many studies have found that GSDMD is necessary for neutrophil IL-1β release [20,36], and in our study, we also found that IL-1β and IL-18 levels in the lungs of LPS-challenged mice were also reduced after neutrophil GSDMD-specific knockout. Thus, the secretion of IL-1β and IL-18 by GSDMD cleavage in neutrophils might also be a cause of ARDS.…”
Section: Discussionsupporting
confidence: 81%
“…Nonetheless, our study did not exclude other mechanisms that might also be involved in the GSDMD-mediated lung injury upon LPS challenge. Many studies have found that GSDMD is necessary for neutrophil IL-1β release [20,36], and in our study, we also found that IL-1β and IL-18 levels in the lungs of LPS-challenged mice were also reduced after neutrophil GSDMD-specific knockout. Thus, the secretion of IL-1β and IL-18 by GSDMD cleavage in neutrophils might also be a cause of ARDS.…”
Section: Discussionsupporting
confidence: 81%
“…Recent functional studies have demonstrated that human and murine neutrophils express high levels of GSDMD 54,56,75,78,79,99–106 and GSDME 78,102 protein; analyses of the possible expression of the other GSDM proteins in neutrophils have not been reported. Although comprehensive transcriptomic profiling of GSDM family expression in neutrophils has not been reported, our RNA‐Seq analysis of FACS isolated (>99%) murine neutrophil populations revealed high gene expression of GSDME and GSDMD, but no other murine GSDM family members (E. Pearlman and G.R.…”
Section: Inflammasomes and Gasdermins As Critical Regulators Of Pyrop...mentioning
confidence: 99%
“…Notably, a very recent study by Chauhan et al 75 reported that ATP‐ or nigericin‐induced activation of NLRP3 inflammasomes in murine neutrophils resulted in a GSDMD‐dependent secretion of IL‐1β but also GSDMD‐dependent uptake of SytoxGreen (a DNA‐intercalating dye similar to propidium) indicative of accumulated N‐GSDMD pores in the plasma membrane. However, the number of SytoxGreen + neutrophils in the stimulated conditions was quite modest (~15% vs. 5–7% in unstimulated neutrophils) even after 100 minutes.…”
Section: Neutrophil Inflammasome Signaling Pathways That Facilitate R...mentioning
confidence: 99%
“…Neutrophils are the first and most plentiful cells that permeate through the inflammatory region, where they can receive DAMPs ( 98 ) and then release many secretory vesicles containing proinflammatory factors and phagocytose pathogens to antagonize inflammation ( 99 ). Researchers have proven that neutrophils are an important source of IL-1β in both mice and human and that higher mRNA and protein levels of AIM2, ASC, and caspase-1 and AIM2 can induce GSDMD pyroptosis in neutrophils ( 85 , 86 ). AIM2-mediated secretion of IL-1β upregulates IL-17 release by T cells of a murine model of atherosclerosis, which then drives chemokines such as CXC motif chemokine ligand 1 (CXCL1) and CXCL2 to recruit more neutrophils during inflammation ( 87 ).…”
Section: Activation Of the Aim2 Inflammasome In Immune Cellsmentioning
confidence: 99%